1979
DOI: 10.1073/pnas.76.3.1368
|View full text |Cite
|
Sign up to set email alerts
|

Allelic pairing and gene regulation: A model for the zeste—white interaction in Drosophila melanogaster

Abstract: Data are presented that indicate that the z locus of Drosophila melanogaster represses w locus activity, but the repression is effective only on paired or physically adjacent w loci. Various mutant alleles of z and w were combined in a series of different doses to determine the effect of dosage and physical position in the nucleus on gene expression. In z/z individuals, paired white alleles fail to be expressed, while unpaired alleles are expressed normally. The results are discussed in terms of a model postul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
44
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(50 citation statements)
references
References 7 publications
6
44
0
Order By: Relevance
“…In the bithorax locus transvection induced an enhancement of the mutant phenotype of alleles in the trans position, and was thought to be due to the prevention of the opposition of homologous alleles (Lewis, 1954;Gelbart, 1982). In addition to the effect at the bithorax complex (BX-C; map location 3-58.8) transvection has been observed in the decapentaplegic complex (DPP-C; 2-4.0) (Gelbart, 1982) and at the white locus (w; 1-1.5) (Green, 1967;Gelbart, 1971Gelbart, , 1982Jack and Judd, 1979;Gelbart and Wu, 1982;Zachar et a!., 1985;Smolik-Utlaut and Gelbart, 1987). Synapsis-dependent trans regulation of gene activity has also been suggested for the salivary gland glue protein 4 (Sgs-4) gene by Korge (1981).…”
Section: Introductionmentioning
confidence: 99%
“…In the bithorax locus transvection induced an enhancement of the mutant phenotype of alleles in the trans position, and was thought to be due to the prevention of the opposition of homologous alleles (Lewis, 1954;Gelbart, 1982). In addition to the effect at the bithorax complex (BX-C; map location 3-58.8) transvection has been observed in the decapentaplegic complex (DPP-C; 2-4.0) (Gelbart, 1982) and at the white locus (w; 1-1.5) (Green, 1967;Gelbart, 1971Gelbart, , 1982Jack and Judd, 1979;Gelbart and Wu, 1982;Zachar et a!., 1985;Smolik-Utlaut and Gelbart, 1987). Synapsis-dependent trans regulation of gene activity has also been suggested for the salivary gland glue protein 4 (Sgs-4) gene by Korge (1981).…”
Section: Introductionmentioning
confidence: 99%
“…This allele was isolated as a gain-of-function (g-o-f) dominant suppressor of an allele of the X-linked zeste gene, called z 1 , which represses expression from the white 1 (w 1 ) eye-color gene in a manner that is sensitive to whether the w 1 gene is paired with another w 1 gene ( Jack and Judd 1979; reviewed by Wu and Goldberg 1989;Pirrotta 1991;Kassis 2002). For example, the eye color of z 1 w 1 / z 1 w 1 females is yellow instead of wild-type red because the somatic homolog pairing that occurs in Drosophila (Stevens 1907(Stevens , 1908Metz 1916;Lewis 1954 (Wu 1984;Adler et al 1989;Wu and Howe 1995).…”
mentioning
confidence: 99%
“…For example, studies of transvection at Ubx (Lewis 1954), dpp (Gelbart 1982), eya (Leiserson et al 1994), and Abd-B (Sipos et al 1998) showed that 0.2-0.8% and possibly more of chromosomes that had been exposed to 4000-4500 rad of X rays carried a transvection-disrupting rearrangement. In contrast, transvection at white (w) ( Jack and Judd 1979;Smolik-Utlaut and Gelbart 1987;Gubb et al 1997) and a second example of transvection at Abd-B (Hendrickson and Sakonju 1995;Hopmann et al 1995) are associated with small critical regions; only chromosomal rearrangements that break very close to white or Abd-B are able to disrupt transvection.…”
mentioning
confidence: 99%
“…org), or those that disrupt transvection at both loci. Transvection at white can be observed in a zeste 1 (z 1 ) background, which does not affect unpaired white genes but causes paired white genes to be repressed, producing flies with eyes that are yellow in color instead of wild-type red ( Jack and Judd 1979;reviewed by Pirrotta 1991). Interestingly, mutations at zeste have also been shown to disrupt transvection-associated phenotypes at dpp (Gelbart and Wu 1982), eya (Leiserson et al 1994), and Ubx (Lewis 1954).…”
mentioning
confidence: 99%